Similes of Woman and Man in the Book of Song of Songs - Dayan Domisianus Toar; Barli Bram (Al-Lisan: Jurnal Bahasa, 2023)
The study aimed to identify the types of similes of woman and man in the Bible book, Song of Songs, and their underlying principal metaphor. While the Songs of Songs’ figurative language is commonly analyzed through the lens of historical and pure literary approaches, the authors analyzed it using the cognitive linguistics framework. Qualitative content analysis was employed as the method. The findings showed that the similes of the woman (35) outnumbered similes of the man (12), and they grouped into 7 types, namely Architectural, Artefactual, Botanical, Celestial, Comestible, Topographic, and Zoomorphic. The similes are mostly zoomorphic (13) and botanical (12). The similes represented the woman mainly as A Protected City, while the man as A City Protector. It was argued that the underlying metaphor of all similes of woman and man in the Song of Songs is Love Is Protection. The findings may contribute as an alternative way of reading and understanding figurative language in the Song of Songs.